Behavioral Approach Towards Islamic Finance in Pakistan: A Preliminary Investigation - Nawaz, Huma; Nawaz, Shamaila (Islamic Banking and Finance Review, 2025)
Islamic financial practices emphasize on the instillation of Islamic laws in the practices that are considered ethical in this world. The purpose of this paper is to determine the factors of Islamic banking promotion among Pakistani educated community. Demographic factors, attitude and financial recommendation items were examined to determine the influence of these factors in promoting ethical financial instruments. The paper follows quantitative research in nature. It explored more than two theories. After a conceptual analysis of the theory of reasoned action (TRA) and theory of planned behavior, this paper investigates the impact of ethical behavior towards the selection of Islamic financial products and services in Pakistan. The descriptive and inferential techniques were used on 194 respondents of Pakistan. There are some positive and significant relationships between behavior intuition and promotion of Islamic products and services. To trigger a specific financial sector of an economy, managers in the Islamic banks should account best individual outcome on ethical decision, rule-based ethical decisions in which the rational approach is not adopted. This study implies that promotion of financial services is achieved when there is improvement in awareness about ethical financial products and services.